2009
DOI: 10.1111/j.1475-097x.2009.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the effect of coffee on hypolagesia associated with transcutaneous electrical nerve stimulation

Abstract: Transcutaneous electrical nerve stimulation (TENS) is a non-invasive, inexpensive analgesic technique used to relieve pain. It has been suggested that caffeine, an adenosine antagonist, may interfere with TENS action. This double-blind controlled pilot study investigated the effect of coffee on response to TENS in healthy human participants experiencing experimentally induced pain. Twelve participants (7 female, age range = 20-41 years) took part in two experiments separated by 24 h. Each experiment lasted 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(65 reference statements)
0
1
1
Order By: Relevance
“…We found that higher current amplitude was necessary to achieve a strong non‐painful sensation for non‐invasive interactive neurostimulation compared with TENS. However, current amplitudes to achieve a strong non‐painful TENS sensation were lower than previous studies by ourselves (32) and others (33), which tend to be between 18 and 25 mA. Lower than expected values may be because the participants in the TENS group did not increase TENS intensity to the appropriate level, despite clear instructions.…”
Section: Discussioncontrasting
confidence: 69%
“…We found that higher current amplitude was necessary to achieve a strong non‐painful sensation for non‐invasive interactive neurostimulation compared with TENS. However, current amplitudes to achieve a strong non‐painful TENS sensation were lower than previous studies by ourselves (32) and others (33), which tend to be between 18 and 25 mA. Lower than expected values may be because the participants in the TENS group did not increase TENS intensity to the appropriate level, despite clear instructions.…”
Section: Discussioncontrasting
confidence: 69%
“…37 Therefore, dietary caffeine consumption may interfere with this mechanism, but this has not been confirmed by preliminary clinical investigations. 41 Interestingly, TENS frequencies are in the same range as those inducing an adenosine-dependent inhibition of GABAergic transmission on neurons of lamina II. 24 As indicated in the previous paragraph, this inhibition and the conditions of its engagement depend on the excitatory or inhibitory nature of the postsynaptic neuron.…”
Section: Activity-dependent Activation Of Adenosine Receptorsmentioning
confidence: 99%